Allergy-unrelated eosinophil activation in the peripheral blood of children with neurodevelopmental disorders - Ji, Wenjing; Li, Muhan; Yang, Chenlu; Lu, Yuanyuan; Liang, Aimin (Frontiers in Neurology, 2025)
BackgroundNeurodevelopmental disorders (NDDs) are increasingly associated with immune dysregulation, but eosinophil activation independent of allergic diseases remains unexplored in this population.MethodsPeripheral-blood eosinophil cationic protein (ECP) mRNA expression was quantified in 55 children with NDDs—including developmental delay (DD), autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), communication disorder, and tic disorder—and 32 typically developing controls. Participants with allergies or recent infections were excluded.ResultsThe NDDs group exhibited significantly elevated ECP mRNA levels compared to controls, with median values of 165.87 copies/μL vs. 56.92 copies/μL (p < 0.001). Subgroup analyses confirmed increases in DD (p = 0.020), ASD (p = 0.002), and ADHD (p = 0.014), though no inter-subgroup differences were observed. Multivariate analysis identified NDDs as an independent predictor of ECP elevation (p = 0.048). Two high-ECP subjects harbored copy number variants affecting neuroimmune genes ADA and LAT. No correlations emerged between ECP levels and clinical behavioral scores.ConclusionThese findings establish a novel association between non-allergic eosinophil activation and NDDs, implicating neuroimmune crosstalk in disease pathogenesis and supporting ECP as a potential biomarker.